Analisis Pengaruh Fenomena Iklim El-Nino dan La-Nina terhadap Curah Hujan di Kalimantan Tengah - Nugraheni, Melly; Zakaria, Ahmad (Jurnal Teknik Sumber Daya Air, 2023)
Central Kalimantan is one of the regions in Indonesia affected by El Nino and La Nina climate anomalies. This study was conducted to determine the effect of El Nino and La Nina climate anomalies or deviations on rainfall in Central Kalimantan. The purpose of this study was to look at the areas that have the most influence caused by El Niño and La Nina climate anomalies. This study used daily rainfall data from the Meteorology, Climatology and Geophysics Agency (BMKG) station and also the Tropical Rainfall Measurement Mission (TRMM) satellite in Central Kalimantan with a data range of 22 years, from 1998 to 2019. Spectral methods are used as modeling and use the Fast Fourier Transform (FFT) program to obtain rainfall spectrum data. Then the amplitude value is obtained and the data comparison is carried out to determine the value of the correlation relationship. The results of data analysis according to the results of Fast Fourier Transform (FFT) obtained that the area that has the highest influence due to El Nino and La Nina climate anomalies or deviations based on BMKG and TRMM data is at the H. Asan station. The dominant frequency period of recurrence for BMKG data is 3.74 years with an amplitude value of 1.4641 mm and TRMM data is 2.80 years with an amplitude value of 0.9829 mm.